Anti-microbial, anti-cancer and immunomodulatory properties of proteinaceous postbiotic metabolite produced by Lactobacillus plantarum I-UL4 - Muhamad Zakuan, Noraina; Foo, Hooi Ling; Saiful Yazan, Latifah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Bacteria and their metabolites are shown to be a potential therapeutic agent for cancer treatment. Much attention has been directed to Lactic acid bacteria (LAB) which exhibits several killing mechanisms via invasion and colonization of solid tumors. Discovery of the characteristics of postbiotic metabolites that exert the same probiotic effects has attracted immense attention towards anti-cancer effect. It is known that LAB improves health and composition of microbiota in the gut. Supplementation of LAB is proven to enhance the host immunity and modulation of the immune system to fight diseases including cancers. Lactobacillus plantarum I-UL4 is the LAB species isolated from Malaysian fermented food, Tapai Ubi which capable of producing bioactive metabolic products. In this review, the properties of UL4-PPM will be discussed including anti-microbial, anti-cancer and immunomodulatory effects. Overall, it would be beneficial to discover the potential effects of UL4-PPM to possibly serve as an alternative treatment for cancer.